منهج العربيَّة في التَّعبير عَن العدَد Expressing Numbers in The Arabic Language - (Salih Mahgoub Mohamed Eltingari) (At-Tajdid - Intellectual Refereed Journal, 2014)
سَعَى هذا البحثُ من خلال المنهج الوصفيّ الاستقرائيّ إلى تبيان المنهج الذي سلكته اللُّغة العربيَّة للتًّعبير عن العدد، وقد بيّن البحث رسوخ فكرة أنْ يأتي المفرد أولاً عند القُدامَى ثم يأتي المثنى، والجمع بأنواعه وفقاً للتّرتيب السَّابق. ومن سَعَة العربيَّة التعبير بالمفرد عن الجمع، وقد احتفظت العربيَّة بالمثنى بوصفه مرحلة أولى للجمع، وقد يخرج المثنى عن أصله فيدلُّ على المفرد. أمّا الجمع فقد ثبت أنّه شريك المثنى من جهة الجمع والضًّم، ويختلف عنه في الكمَّية والمقدار. وللجمع نوعان: جمع صحيح، وجمع تكسير. وتوصَّل البحث إلى نتائج من أهمِّها: سلامة تصنيف القُدامَى الاسمَ إلى مفرد، ومثنى، وجمع، وصلاحية الجمع السَّالم بنوعيه للقليل والكثير وفقا ًللسِّياق الذي وردَ فيه، أما استخدام جمع القلًّة موضع جمع الكثرة أو العكس فهو من قبيل المجاز. الكلمات الأساسية: العدد، المفرد، المثنّى، جمع صحيح، جمع تكسير. ________________________________________________ This study has attempted to bring to light the modes of expressing numbers in the Arabic language by applying a descriptive and inductive method. It has shown the deep-rootedness among ancient Arabs of the sequence of the singular (mufrad), the dual (muthannÉ) and the plural (jamÑ) in its different kinds. An aspect of the richness of the Arabic language is to express the plural by the singular and assigning the dual a middle position between the singular and the plural, though the dual may also denote the singular. It has also been shown that one common feature between the plural and the dual is to combine and conjoin, yet it differs from it in terms of quantity. The plural has two forms: sound plural and broken plural. Of the findings arrived at in this study is the soundness of classical categorization nouns into singular, dual and plural and the suitability of the plural (together with its varieties) for both fewness and multitude according to the context. The use of fewness plural in place of multitude plural and vice-versa is a matter of allegory. Key words: Numbers, singular, plural, dual, sound plural, broken plural..